GAYA KOGNITIF FIELD DEPENDENT DAN TINGKAT PEMAHAMAN KONSEP MATEMATIS ANTARA MODEL PEMBELAJARAN LANGSUNG DAN STAD - Agung Putra Wijaya (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
This correlational research was aimed to find out whether there is a positive correlation between field dependent cognitive style and mathematical conceptual understanding of students who was  taught by direct instructinand STAD model. The population of this research was all students of grade eighth of a Public Junior High School in Lampung Selatan. By cluster random sampling technique, there were two classes of research sample. The test method was applied to collect the data. The instruments of this research were GEFT and test of mathematical conceptual understanding of line equation material. Based on the result of hypotesis test, it was concluded that (1) there is a positive correlation between field dependent cognitive style and mathematical conceptual understanding on students who was taught by direct learning model and (2) there is no positive correlation between field dependent cognitive style and mathematical conceptual understanding on students who was taught by STAD learning model. This result implies that learning model affects mathematical conceptual understanding of student who has field dependent cognitive style. Key Words: field dependent, conceptual understanding, direct instruction, STAD